PREPARATION OF SPECIALISTS OF SOCIAL SPHERE FOR WORK IN AIRPORTS - Санжаровець, В. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
Social Work at the airport is to offer passengers the airport social services. The main methodological position is that people are under stress, characterized by a particular set of characteristics in appearance and behavior. In such circumstances, a passenger in his actions attracted the attention and help him with the documents of carriage or psychologically, can a person whom he trusts